2023
DOI: 10.37934/arfmts.101.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of New Formulation of Hybrid Nanofluid-based Minimum Quantity Lubrication (MQL) from Modified Jatropha Oil as Metalworking Fluid

Abstract: As a metalworking fluid, vegetable-based crude jatropha oil (CJO) was used in place of petroleum-based oil. The use of petroleum-oil-based metalworking fluids poses significant environmental and health concerns. Furthermore, it has a large amount of free fatty acid (FFA), promoting physical damage. This research targets to substantially evaluate the modified jatropha nanofluids formulation as a metalworking fluid for machining processes. CJO was chemically altered using the esterification and transesterificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This trend shows that temperature plays an important role in kinematic viscosity. According to the findings of Sabri et al, [21], it was observed that an increase in temperature led to an accelerated dispersion of molecules in the lubricant samples. Furthermore, there are significant cohesive forces between the molecules of a liquid, which are considerably closer together compared to those of a gas.…”
Section: Kinematic Viscosity and Viscosity Index (Vi)mentioning
confidence: 93%
See 1 more Smart Citation
“…This trend shows that temperature plays an important role in kinematic viscosity. According to the findings of Sabri et al, [21], it was observed that an increase in temperature led to an accelerated dispersion of molecules in the lubricant samples. Furthermore, there are significant cohesive forces between the molecules of a liquid, which are considerably closer together compared to those of a gas.…”
Section: Kinematic Viscosity and Viscosity Index (Vi)mentioning
confidence: 93%
“…The observed phenomenon might be attributed to the presence of a double bond in the fatty acid chain, which leads to an increase in rigidity. Consequently, this hinders the close arrangement of fatty acid chains [21]. The incorporation of nanoparticles into MPOs leads to enhanced acid value in comparison to the MPO.…”
Section: Acid Valuementioning
confidence: 99%